2009
DOI: 10.1021/jm801306g
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Virtual Screening Cascade Protocol to Identify Potential Trypanothione Reductase Inhibitors

Abstract: The implementation of a novel sequential computational approach that can be used effectively for virtual screening and identification of prospective ligands that bind to trypanothione reductase (TryR) is reported. The multistep strategy combines a ligand-based virtual screening for building an enriched library of small molecules with a docking protocol (AutoDock, X-Score) for screening against the TryR target. Compounds were ranked by an exhaustive conformational consensus scoring approach that employs a rank-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 49 publications
0
28
0
3
Order By: Relevance
“…Additional evidence that the quinoline and 9-aminoacridine hits identified in the ELEC system are particularly good leads for further development is based on previous studies of these compounds as potential antimalarial compounds. Here it was shown that these relatively basic compounds with high LogP (lipophilicity) values favor their intracellular transport, which is responsible for the observed activity and selectivity (54)(55)(56)(57). Furthermore, it has been demonstrated that certain acridines (54,(58)(59)(60)(61) can inhibit DNA synthesis in Leishmania and/or Plasmodium, interfering with DNA transcription (topoisomerase II).…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence that the quinoline and 9-aminoacridine hits identified in the ELEC system are particularly good leads for further development is based on previous studies of these compounds as potential antimalarial compounds. Here it was shown that these relatively basic compounds with high LogP (lipophilicity) values favor their intracellular transport, which is responsible for the observed activity and selectivity (54)(55)(56)(57). Furthermore, it has been demonstrated that certain acridines (54,(58)(59)(60)(61) can inhibit DNA synthesis in Leishmania and/or Plasmodium, interfering with DNA transcription (topoisomerase II).…”
Section: Discussionmentioning
confidence: 99%
“…37,42,44 Alguns exemplos ilustram a aplicação destas técnicas na identificação de novos esqueletos químicos (scaffold hopping). 40,45 Etapas de LBVS Em geral, os métodos de LBVS se fundamentam em estudos de similaridade ou em modelos construídos a partir de conjuntos de ligantes e não ligantes. 40,43 As buscas por similaridade química envolvem a geração de impressões digitais moleculares para todas as moléculas das bases de dados.…”
Section: Triagem Virtual Baseada Na Estrutura Do Liganteunclassified
“…Outrossim, esta técnica é útil na análise prévia de grandes bases de dados, permitindo a geração de coleções dirigidas para avaliações posteriores, experimentais ou computacionais. 15,17,41,45 …”
Section: Figura 3 Estratégias De Lbvs: A) Lbvs Baseada Em Similaridaunclassified
See 1 more Smart Citation
“…Some experimental as well as in silico attempts have been made to identify inhibitors or subversive substrates for various molecular targets (Krauth-Siegel and Inhoff, 2003;Perez-Pineiro et al, 2009). The enzyme Tryparedoxin Peroxidase (Try P) of Leishmania braziliensis is a 199 amino acid enzyme with a molecular weight of approximately 22.5 kDa.…”
Section: Introductionmentioning
confidence: 99%